Adsorb-Catalytic Removal of PH3 and H2S in Yellow Phosphorus Off-Gas by Metallic Modified Activated Carbon. Issue 2 (March 2020) - Li, Rui; Wang, Botao; Yao, Mei; Wang, Fang; Liu, Tiancheng; Liu, Chenhui; Gao, Jiyun; Ning, Ping; Jia, Lijuan
Abstract: Activated carbon modified with Cu 2+ and Co 2+ was used to remove PH3 and H2 S from yellow phosphorus off-gas. An orthogonal experiment was carried out to identify the superiority order of influencing factors and the optimal experimental parameters. For PH3, the superiority order was temperature > oxygen content > parch temperature > impregnant concentration (Cu 2+ ) > flow rate > diameter, whereas, for H2 S, it was reaction temperature > oxygen content > impregnant concentration > parch temperature > diameter > flow rate. Following were the optimal experimental parameters for both PH3 and H2 S: reaction temperature, 95°C; impregnant concentration (Cu 2+ ), 0.25 mol/L; diameter of metallic modified activated carbon (MMAC), 3.5 mm; oxygen content, 1%; parch temperature, 300°C; and flow rate, 0.4 L/min. Regeneration of MMAC was effective for PH3 but not compelling for H2 S. The activation energy and reaction orders were calculated, and the transmission process was evaluated to assess the characteristics of the dynamics of the adsorb-catalytic reaction. The reaction orders were -0.8 and -0.76 for PH3 and H2 S and the average activation energies were 1247.6 and 134.4 J/mol for PH3 and H2 S, respectively. The adsorb-catalytic reaction was fast, and decreasing transmission resistance can play a key role in improving the performance of MMAC.